Planejamento, síntese e avaliação da atividade antimalárica de uma série de piridilpiperazinas - Oliveira, Douglas Davison da Silva (2023)
Malaria is a parasitic disease that affects millions of people and causes thousands of deaths worldwide. Currently, the treatment for the most severe form of malaria involves the use of an artemisinin-based combination therapy. However, recent reports from the WHO indicate the emergence of strains resistant to this treatment, increasing the urgent need to discover new anti-malarial drugs. This study aims to contribute to the discovery of new antimalarial drug candidates, based on an investigation of the relationship between the structure and antimalarial activity of pyridylpiperazine derivatives. An optimization of this class of compounds against Plasmodium falciparum was performed, exploring chemical modifications in the toluyl and amide fragments of the initial hit 1. After confirming the crucial role played by the aryl fragment in the antiplasmodial activity, the substitution of the ortho-methyl group of hit 1 with halogenated fragments resulted in four analogs with more promising properties in terms of potency and expected pharmacokinetic profile. The introduction of endocyclic nitrogens into this fragment identified two more optimized compounds, 27 and 30, which are expected to be more metabolically stable than hit 1. Additional cytotoxicity evaluations in HepG2 cells revealed the series' selective profile, as most compounds showed low levels of cytotoxicity. Furthermore, the potency results against the drug-resistant Dd2 strain of P. falciparum demonstrated that the compounds maintained their antiplasmodial activity. Evaluations of Ligand Lipophilicity Efficiency and in silico ADME predictions provided a satisfactory profile for most compounds, ultimately identifying the four optimized compounds, 18, 20, 27, and 30, as promising candidates for subsequent optimization of this series against Plasmodium falciparum. An initial screening was conducted to assess the potency profile of derivatives with modifications in the amide fragment against P. falciparum. The results obtained by testing the derivatives at three different concentrations (200, 20, and 2 μM) revealed a suitable profile for further IC50 determination studies against the sensitive strain of P. falciparum (3D7). These findings are encouraging and justify future research to more accurately determine the efficacy and optimal dosage of these compounds against Plasmodium falciparum. It is expected that these discoveries will contribute to the development of new treatments against malaria.